The Integration of Renewable Energy Sources into Mechanical Systems, Focusing on Efficiency and Reliability - A Case Study - Khan, Saidul Islam; Dodaev, Zohar Al; Haque, Abrarul (Control Systems and Optimization Letters, 2024)
The main objective of this review to analyze the efficiency and reliability of renewable energy technologies when integrated into mechanical infrastructure. The concerns of energy sustainability and environmental impact can be effectively addressed by incorporating renewable energy sources into mechanical systems. The use of renewable energy technology to mechanical systems is examined in this case study, with an emphasis on improving dependability and efficiency. The study explores the integration of solar, wind, and hydroelectric power generation into mechanical systems, such as HVAC (heating, ventilation, and air conditioning) systems, industrial machinery, and transportation systems, by means of a thorough analysis of a practical application. Studying the integration of solar, wind and hydroelectric thermal energy to raise building HVAC systems' dependability and efficiency are the main concern of this review. The design, implementation, and optimization of renewable energy systems are important topics covered because they optimize energy output while maintaining dependability and compatibility with the mechanical infrastructure already in place. In addition, the study assesses the technological issues, environmental advantages, and economic feasibility of integrating renewable energy sources, offering insights into successful strategies and difficulties faced. This case study is to educate decision-makers, engineers, and stakeholders about the potential and factors for sustainable energy solutions in mechanical engineering applications by examining the effectiveness and dependability of renewable energy integration in mechanical systems.